2002
DOI: 10.1038/sj.dmfr.4600719
|View full text |Cite
|
Sign up to set email alerts
|

Appearance, location, course, and morphology of the mandibular incisive canal: an assessment on spiral CT scan.

Abstract: A well-defined incisive canal could be detected in the majority of spiral CT scans. Its radiographic detection remained lower than for the mandibular canal or mental foramen, but higher than for the visibility of the lingual foramen. Visualisation of the incisive canal and the occasional presence of an anterior looping, demonstrates the potential value of cross-sectional imaging of the anterior mandible for presurgical planning purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
133
4
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 13 publications
14
133
4
19
Order By: Relevance
“…Despite these discrepancies, there are numerous reports that confirm the presence of MIC in the region located between both mental foramina, through anatomical dissection (Uchida et al, 2007;Vu et al;Xu et al, 2015) and cone beam tomography imaging. (Jacobs et al, 2002;Kajan & Salari, 2012;Orhan et al, 2014). The anatomical characteristics of this and other structures could be associated with race (Xu et al).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these discrepancies, there are numerous reports that confirm the presence of MIC in the region located between both mental foramina, through anatomical dissection (Uchida et al, 2007;Vu et al;Xu et al, 2015) and cone beam tomography imaging. (Jacobs et al, 2002;Kajan & Salari, 2012;Orhan et al, 2014). The anatomical characteristics of this and other structures could be associated with race (Xu et al).…”
Section: Introductionmentioning
confidence: 99%
“…İmplantın başarısız olduğu osseointegrasyonun gerçekleşmediği koşullarda da implantın uzaklaştırılması sırasında oluşacak postoperatif ağrı da olası komplikasyonlar arasında sayılmaktadır. 17 Diş hekimliğinde iki boyutlu konvansiyonel görüntüleme sistemlerinden doğru bir tanı ve tedavi planlaması için sıklıkla yararlanılmaktadır. Ancak mandibular insiziv kanalın morfolojik özelliklerini ortaya koymada 2 boyutlu radyografiler çoğunlukla yetersiz kalmaktadır.…”
Section: 2unclassified
“…Dental implant uygulamaları küçük cerrahi işlemler gibi görülse de, literatürde mandibular anterior bölgeye implant yerleştirilmesi sırasında veya birkaç saat sonrasında ortaya çıkan ciddi kanama komplikasyonlarından bahsedilmektedir. 24 Bu tip kanamaların nedeni, lingual bölgeden kemik kanallarına girerek mandibulayı besleyen ve ağız tabanında geniş anastomozlar oluşturan sublingual arter dallarının implant cerrahisi sırasında zarar görmesidir. 25 Bu komplikasyon hemen işlem sırasında belirti vermemekte birkaç saat sonra ortaya çıkabilmekte ve büyük bir hematom oluşturarak üst solunum yolu tıkanmasına neden olabilmektedir.…”
Section: 2unclassified
See 1 more Smart Citation
“…The study suggested that the lingual foramen was a consistent finding to the lingual side of the mandible in the midline, being present in over 99% of the dried specimen examined. The foramen was definitely visible in 81% and 82% in Makris (Makris et al, 2010) based on CBCT and Jacobs (Jacobs et al,. 2002) based on CT studies, respectively.…”
Section: Importance Of Pre-surgical Assessmentmentioning
confidence: 99%